2021
DOI: 10.2340/00015555-3824
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Tumour Characteristics of Keratoacanthoma in a Large, Community-based Cohort Study from Queensland, Australia

Abstract: Keratoacanthomas are common keratinocyte skin tumours. However, there is little community-based data published on the clinical features of keratoacanthoma. The aim of this study was to describe the patient and tumour characteristics of keratoacanthomas, as well as their treatment patterns. Data were obtained from the QSkin Sun and Health study, a prospective cohort of 40,438 randomly sampled and consented participants aged 40–69 years in Queensland, Australia. In 2010, a baseline survey collected data, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, genomic differences, prognosis, and metastasis rates that exist between KA and cSCC suggest that these two conditions do not belong to the same category [3][4][5]. Moreover, reports showing a high incidence of KA (409/ 100,000 person-years) concentrated among residents of Queensland, Australia [6] also suggest that notable differences are present between KA and cSCC. Alternatively, such findings may likely grossly underestimate the incidence of KA due to the misclassification of these lesions as welldifferentiated cSCC, underreporting, and/or spontaneous regression of KA prior to diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, genomic differences, prognosis, and metastasis rates that exist between KA and cSCC suggest that these two conditions do not belong to the same category [3][4][5]. Moreover, reports showing a high incidence of KA (409/ 100,000 person-years) concentrated among residents of Queensland, Australia [6] also suggest that notable differences are present between KA and cSCC. Alternatively, such findings may likely grossly underestimate the incidence of KA due to the misclassification of these lesions as welldifferentiated cSCC, underreporting, and/or spontaneous regression of KA prior to diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent World Health Organization (WHO) classification of cutaneous tumors, keratoacanthoma was classified as a low-grade SCC, suggesting that it is biologically stable and that some keratoacanthomas evolve into conventional SCCs with a gradual loss of capacity for spontaneous regression ( 6 ). Individuals with keratoacanthoma are most likely to be men aged ≥60 years ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of keratoacanthoma has not been completely elucidated; however, causative factors include immunosuppression, ultraviolet (UV) or X-ray exposure, drug treatments, foreign bodies, various traumas ( 5 ), and human papillomavirus DNA. Male sex, older age, smoking, and alcohol consumption have been reported to be hazardous variables ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Kolmodin and colleagues ( 1 ), which raises some interesting issues. The authors state “Importantly, this study found a high proportion of histologically regressing tumours, indicating that spontaneous resolution of KA may be common.” We find this statement confusing.…”
mentioning
confidence: 99%
“…We are grateful for the comments from Mazzoni & Muir on our article ( 1 ) on the occurrence of keratoacanthoma (KA) in Queensland, Australia. We concur with their input and appreciate their contribution.…”
mentioning
confidence: 99%